The Association of Cognitive Ability with Right‐wing Ideological Attitudes and Prejudice: A Meta‐analytic Review. Issue 6 (1st October 2015) - Onraet, Emma; Van Hiel, Alain; Dhont, Kristof; Hodson, Gordon; Schittekatte, Mark; De Pauw, Sarah
Abstract: The cognitive functioning of individuals with stronger endorsement of right‐wing and prejudiced attitudes has elicited much scholarly interest. Whereas many studies investigated cognitive styles, less attention has been directed towards cognitive ability . Studies investigating the latter topic generally reveal lower cognitive ability to be associated with stronger endorsement of right‐wing ideological attitudes and greater prejudice. However, this relationship has remained widely unrecognized in literature. The present meta‐analyses revealed an average effect size of r  = −. 20 [95% confidence interval (95% CI) [−0.23, −0.17]; based on 67 studies, N   = 84 017] for the relationship between cognitive ability and right‐wing ideological attitudes and an average effect size of r   = −.19 (95% CI [−0.23, −0.16]; based on 23 studies, N   = 27 011) for the relationship between cognitive ability and prejudice. Effect sizes did not vary significantly across different cognitive abilities and sample characteristics. The effect strongly depended on the measure used for ideological attitudes and prejudice, with the strongest effect sizes for authoritarianism and ethnocentrism. We conclude that cognitive ability is an important factor in the genesis of ideological attitudes and prejudice and thus should become more central in theorizing and model building. Copyright © 2015 European Association of Personality Psychology